VPAC1 and VPAC2 Receptor Heterozygosity Confers Distinct Biological Properties to BV2 Microglial Cells - Xin Ying Rachel Song; Margo Iris Jansen; Rubina Marzagalli; Giuseppe Musumeci; Velia D’Agata; Alessandro Castorina (Cells)
Microglial cells, the resident immune cells of the central nervous system (CNS), are essential for maintaining CNS homeostasis. Dysregulation of microglial function is implicated in the pathogenesis of various neurodegenerative diseases. Vasoactive intestinal polypeptide receptors 1 and 2 (VPAC1 and VPAC2) are G-protein-coupled receptors (GPCRs) expressed by microglia, with their primary ligands being pituitary adenylate cyclase-activating polypeptide (PACAP) and vasoactive intestinal peptide (VIP). However, the specific roles of VPAC-type receptors in microglial regulation remain poorly understood. In this study, we generated VPAC1+/− and VPAC2+/− BV2 microglial cell lines using CRISPR-Cas9 gene editing and conducted a series of biological and molecular assays to elucidate the functions of these receptors. Our findings demonstrated that both mutant cell lines exhibited a polarized phenotype and increased migratory activity. VPAC1+/− cells showed enhanced survivability and baseline activation of the unfolded protein response (UPR), a protective mechanism triggered by endoplasmic reticulum (ER) stress, whereas this response appeared impaired in VPAC2+/− cells. In contrast, under lipopolysaccharide (LPS)-induced inflammatory conditions, UPR activation was impaired in VPAC1+/− cells but restored in VPAC2+/− cells, resulting in improved survival of VPAC2+/− cells, whereas VPAC1+/− cells exhibited reduced resilience. Overall, our findings suggest that VPAC1 and VPAC2 receptors play distinct yet complementary roles in BV2 microglia. VPAC2 is critical for regulating survival, ER stress responses, and polarization under basal conditions, while VPAC1 is essential for adaptive responses to inflammatory stimuli such as LPS. These insights advance our understanding of microglial receptor signaling and may inform therapeutic strategies targeting microglial dysfunction in neurodegenerative diseases.